Síntese e caracterização de poliuretano à base de Poli(-Caprolactona) reforçado com nanocristais de celulose - Debora Rosa da Silva Souza (2013)
Cellulose nanocrystals (CNC) were prepared from eucalyptus wood pulp and they were used as reinforcement material in a polyurethane polymeric matrix. The polyurethane (PU) was synthesized from poly (-caprolactone)-diol, in one step polymerization. The nanocrystals were obtained by acid hydrolysis with sulfuric acid and the obtained CNC were characterized by scanning electron microscopy, X ray diffraction, infrared spectroscopy and thermogravimetry analysis. The mean values of the length (L) and diameter (D) of the isolated CNC were determined to be 145 ± 25 nm and 6 ± 1.5 nm, respectively, giving an aspect ratio (L/D) around 24. For the preparation of PU composite CNC, two different strategies have been used: polymerization in the presence of the cellulose nanoparticles in the reaction medium (in situ) and by casting. The infrared spectroscopy was used to evaluate possible structural changes caused by the presence of CNC in the neat PU. From the in situ polymerization, it was observed that the cellulose nanocrystals nanorods were covalently attached to the polymer chains during the synthesis of the PU prepolymer. The influence of the CNC, in different concentrations, in thermal degradation of the nanocomposites could be investigated by thermogravimetry. The thermal resistance of the nanocomposites increases as the nanocrystal concentration in the sample increases up to the limit of 3%. The effect of the nanocrystals in the presence of phase separation flexible and rigid, the mobility of polymer chains and dispersion of the nanoparticles in the polymer matrix was evaluated by differential scanning calorimetry. Tensile test showed that the elastic modulus increased significantly up to 3% concentration of the nanoparticles. The presence of nanocrystals covalently bound to the matrix changes the mechanical properties of the composite, as observed by the parameters analyzed in this dissertation. The effect of the incorporation of the CNC in the crystallinity of the material was analyzed by X-ray diffraction.